Studies on the interaction between nanodiamond and human hemoglobin by surface tension measurement and spectroscopy methods. Issue 3 (17th February 2017) - Pishkar, Leila; Taheri, Saba; Makarem, Somayeh; Alizadeh Zeinabad, Hojjat; Rahimi, Arash; Saboury, Ali Akbar; Falahati, Mojtaba
Abstract : In this study, a novel method to probe molecular interactions and binding of human hemoglobin (Hb) with nanodiamond (ND) was introduced based on the surface tension measurement. This method complements conventional techniques, which are basically done by zeta potential and dynamic light scattering (DLS) measurements, near and far circular dichroism (CD) spectroscopy, intrinsic and extrinsic fluorescence spectroscopy. Addition of ND to Hb solution increased the surface tension value of Hb–ND complex relative to those of Hb and ND molecules. The zeta potential values reveled that Hb and ND provide identical charge distribution at pH 7.5. DLS measurements demonstrated that Hb, ND, and ND–Hb complex have hydrodynamic radiuses of 98.37 ± 4.57, 122.07 ± 7.88 nm and 62.27 ± 3.70 at pH of 7.5 respectively. Far and near UV-CD results indicated the loss of α-helix structure and conformational changes of Hb, respectively. Intrinsic fluorescence data demonstrated that the fluorescence quenching of Hb by ND was the result of the static quenching. The hydrophobic interaction plays a pivotal role in the interaction of ND with Hb. Fluorescence intensity changes over time revealed conformational change of Hb continues after the mixing of the components (Hb–ND) till 15 min, which is indicative of the denaturation of the Hb relative to the protein control. Extrinsic fluorescence data showed a considerable enhancement of the ANS fluorescence intensity of Hb–ND system relative to the Hb till 60 nM of ND, likely persuaded by greater exposure of nonpolar residues of Hb hydrophobic pocket. The remarkable decrease in T m value of Hb in Hb–ND complex exhibits interaction of Hb with ND conducts to conformational changes of Hb. This study offers consequential discrimination into the interaction of ND with proteins, which may be of significance for further appeal of these nanoparticles in biotechnology prosecution.